Pengaruh Penambahan Doping Cerium terhadap Nilai Bandgap CuO dengan Metode Sol-Gel - Dwiputri, Yumanda; Sanjaya, Hary; Patriela, Miftah (Lembaga Yasin AlSys, 2025)
Copper(II) oxide (CuO) has been recognized as a promising semiconductor material for various applications, such as photocatalysis, sensors, and renewable energy devices. However, its efficiency is often limited by a suboptimal bandgap value. This study aims to analyze the effect of cerium doping on the properties of CuO nanoparticles synthesized through the sol-gel process. The sol-gel method ensures a homogeneous doping distribution and produces nanoparticles with a stable structure. The bandgap energy of CuO nanoparticles was determined through characterization using UV-DRS. Cerium was introduced as a dopant in CuO at a concentration of 0.4 mmol, resulting in a bandgap value of 1.26 eV, whereas undoped CuO exhibited a bandgap of 1.35 eV. The analysis indicates that the Ce doping concentration significantly affects the bandgap of CuO nanoparticles, with a reduction observed at 0.4 mmol compared to undoped CuO. This decrease is attributed to symmetry disruption caused by doping, including oxygen vacancies, structural defects, and the presence of impurities that create additional energy levels within the bandgap. Furthermore, uniform microstrain and a smaller particle size contribute to structural disturbances that also influence the bandgap.